SELF-ESTEEM REMAJA PEREMPUAN DAN KAITANNYA DENGAN PENGASUHAN PENERIMAAN-PENOLAKAN IBU DAN INTERAKSI SAUDARA KANDUNG - Riska, Hotmauli Adina; Krisnatuti, Diah (Jurnal Ilmu Keluarga dan Konsumen, 2017)
Adolescence is development transitional developmental period between childhood and adulthood which includes biological change, cognitive, and social changes. The changes have a direct impact on their evaluation about themselves the attitudes and behavior of adolescents. The purpose of this research was to analyze the influence of self-esteem of girls who as second children and its correlation with parental acceptance-rejection (PAR) of the mother, and sibling interaction, and self-esteem among second-born adolescent girl. Samples of this research were 60 adolescent girls (30 with an older sister and 30 with an older brother). This was a cross-sectional study with purposive sampling. The result of this study showed that warmth dimension of sibling interaction of girl who has an older sister was higher than the girl who has an older brother. There was the positive correlation between girl’s age and mother’s education with acceptance dimension of PAR. Meanwhile, rejection dimension of PAR had a positive correlation with the relative power dimension of sibling interaction. Furthermore, hostility and rejection dimension of PAR had a positive correlation with conflict dimension of sibling interaction. Meanwhile, hostility, neglect, and rejection dimension of PAR had a negative correlation with sibling rivalry dimension of sibling interaction. Correlation test found that self-esteem of girls only correlated significantly with the entire dimension of PAR.